Cancer incidence in the East Azerbaijan province of Iran in 2015-2016: results of a population-based cancer registry - Mohammad Hossein Somi; Roya Dolatkhah; Sepideh Sepahi; Mina Belalzadeh; Jabraeil Sharbafi; Leila Abdollahi; Azin Nahvijou; Saeed Nemati; Reza Malekzadeh; Kazem Zendehdel (BMC, 2018)
Abstract Background Few countries in the Middle East have a population-based cancer registry, despite a clear need for accurate cancer statistics in this region. We therefore established a registry in the East Azerbaijan province, the sixth largest province in northwestern Iran. Methods We actively collected data from 20 counties, 62 cities, and 44 districts for the period between 20th March 2015 and 19th March 2016 (one Iranian solar year). The CanReg5 software was then used to estimate age-standardized incidence rates (ASRs) per 100,000 for all cancers and different cancer types. Results Data for 11,536 patients were identified, but we only analyzed data for 6655 cases after removing duplicates and non-residents. The ASR for all cancers, except non-melanoma skin cancer, was 167.1 per 100,000 males and 125.7 per 100,000 females. The most common cancers in men were stomach (ASR 29.7), colorectal (ASR 18.2), bladder (ASR 17.6), prostate (ASR 17.3), and lung (ASR 15.4) cancers; in women, they were breast (ASR 31.1), colorectal (ASR 13.7), stomach (13.3), thyroid (ASR 7.8), and esophageal (ASR 7.1) cancers. Both the death certificate rate (19.5%) and the microscopic verification rate (65%) indicated that the data for the cancer registry were of reasonable quality. Conclusion The results of the East Azerbaijan Population-based Cancer Registry show a high incidence of cancer in this province, especially gastrointestinal cancers.